Waran pada Initial Public Offerings di Pasar Modal Indonesia - Meidiaswati, Harlina; Sasikirono, Nugroho; Sudana, I Made (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 1 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i01.p11, 2019)
This study aims to determine whether the warrants offerings in the Initial Public Offerings in the Indonesian Capital Market are carried out as a form of staged financing mechanism (Schultz, 1993) or are an attempt to convey signals about the company (Chemmanur and Fulghieri, 1997 ). The study was conducted on 96 IPO companies during the 2010-2013 period on the Indonesia Stock Exchange. The results show that IPOs with warrants are carried out by companies that are younger, have lower profitability, and with the tendency of owners to maintain a lower proportion of ownership after IPO. The results of the OLS analysis show the higher initial return of IPOs with warrants than normal IPOs. Probit analysis shows that the decision to conduct IPOs with warrants is influenced by age and leverage. The results of the study, in general, support the staged financing theory.